Akselerasi Biomassa Kopi Arabika (Coffea Arabica L) Fase Pre Nursery Melalui Perendaman Suspensi Bakteri Endofit Dan Aplikasi Biochar Ampas Kopi - Setya Dila Sri Rahayu; Kabul Warsito; Andi Setiawan (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study discusses the acceleration of the growth of Arabica coffee biomass (Coffea arabica L.) in the pre-nursery phase through endophytic bacterial suspension immersion and application of coffee grounds biochar. The research was conducted in Hamlet 3 of Sampe Cita Village, Kutalimbaru, Deli Serdang, North Sumatra in March-May 2025. The method used was a factorial Group Random Design (RAK) with two factors, namely the soaking time of endophytic bacteria (0, 7, 8, and 9 hours) and the dose of coffee grounds biochar (0, 20, 40, and 60 grams). The results showed that the soaking treatment of endophytic bacteria suspension for 9 hours and the application of coffee grounds biochar gave the best results on the parameters of plant height growth and the number of Arabica coffee seedling leaves in the pre nursery phase. The combination of these two treatments provides a significant increase in biomass compared to other controls and treatments. In addition, the use of coffee grounds waste into biochar can be a waste management solution and reduce environmental pollution. The conclusion of this study is that the synergistic application of endophytic bacteria and biochar of coffee grounds is an environmentally friendly alternative to reduce the need for synthetic fertilizers in Arabica coffee cultivation while encouraging sustainable agricultural systems.